2019
DOI: 10.3892/etm.2019.7230
|View full text |Cite
|
Sign up to set email alerts
|

CD147 mediates transforming growth factor‑β1‑induced epithelial‑mesenchymal transition and cell invasion in squamous cell carcinoma of the tongue

Abstract: Epithelial-mesenchymal transition (EMT) is a physiological process in which epithelial cells attain the motile and invasive characteristics of mesenchymal cells, which results in the development of increased migratory and invasive cell behavior, serving as a vital mechanism of cancer progression. Hence, controlling the EMT for cancer treatment, including head and neck squamous cell carcinoma (HNSCC), is imperative. Among EMT-associated factors, transforming growth factor-β (TGF-β) is a well-established potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…eMT is key to cancer progression and can be induced by TGF-β (14). MG-63 cells were cultured with TGF-β1 (20 ng/ml) to assess its ability to induce eMT in oa cells (15) through the expression of known eMT markers including e-cadherin, vimentin and n-cadherin by western blot analysis ( Fig.…”
Section: Tgf-β1-mediated Emt In Mg-63 Cellsmentioning
confidence: 99%
“…eMT is key to cancer progression and can be induced by TGF-β (14). MG-63 cells were cultured with TGF-β1 (20 ng/ml) to assess its ability to induce eMT in oa cells (15) through the expression of known eMT markers including e-cadherin, vimentin and n-cadherin by western blot analysis ( Fig.…”
Section: Tgf-β1-mediated Emt In Mg-63 Cellsmentioning
confidence: 99%
“…The correlation between the expression of CD147 in tumors and poor prognosis has been widely observed in individuals with solid tumors including HNSCC ( 45 ). It has been reported that CD147 is involved in MMP production, cell invasion, cell proliferation, and EMT in head and neck cancer cells ( 26 , 46 ). Moreover, we have reported that CD147 expression in tongue cancer patients is positively correlated with lymph node metastasis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…While MdA-MB-231 cells were incubated in Leibovitz's 15 medium (L15, E600016-0500; BBI Solutions) with 10% (v/v) FBS and 1% P/S and were cultured in a humidified 37̊C incubator with 100% air. These cells, which were incubated in medium with 0.5% FBS, were treated with 20 ng/ml TGF-β1 (100-21-10; Peprotech, Inc.) for 48 h (24,25). The control cells were incubated in medium with 0.5% FBS and treated with DMSO.…”
Section: Methodsmentioning
confidence: 99%